Peningkatan Kerjasama melalui Pembelajaran Kooperatif Tipe STAD pada Mata Pelajaran Bahasa Indonesia Siswa Kelas II SD - Alivia, Nafa Septian; Utomo, Arief Cahyo (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This study aims to evaluate the effectiveness of using the STAD cooperative learning model in enhancing students' cooperation in the Indonesian language subject. The method used is classroom action research consisting of two cycles with Kemmis and McTaggart design. The subjects of this study are 16 second-grade students at SD Negeri Trangsan 01. Data were collected through observation and interviews, then analyzed descriptively quantitatively and descriptively qualitatively. The results show that the average learning activity of students increased from 54% (less category) in the pre-cycle to 69% (sufficient category) in cycle I. After improvements based on the reflection of cycle I, students' learning activity in cycle II increased to 80% (good category). Therefore, it can be concluded that the STAD cooperative learning model has proven to be effective in enhancing students' cooperation in learning Indonesian. This learning model can be one of the options for teachers to improve students' cooperative attitudes in learning Indonesian.